Hydrogen in Stainless Steel as Killing Agent for UHV: A Review. (2015) - Gupta, Manoj Kumar; Priyadarshi, Abhinav; Khan, Ziauddin
Abstract: Due to the small size of hydrogen atom, its interstitial diffusion accompanied by high mobility of hydrogen atoms in materials. For metals, H diffusivity may reach values as known for ions in aqueous solutions. Thus, thermodynamic equilibrium is reached within comparably short times even at room temperature. Therefore, metal–hydrogen systems are often used as model systems to study physical or chemical properties and their change with concentration. The high mobility of hydrogen further allows studying the impact of defects that usually annihilate at elevated temperatures. Austenitic stainless steels are the most common choice for high vacuum and ultra-high vacuum systems. Not all alloys are suitable; e.g. the free-machining 303 steel contains sulfur, which tends to outgas. Alloys with good weldability under argon arc welding are usually chosen. Stainless steel materials and their properties for manufacturing Ultra-high vacuum (UHV) chambers has found use in the l0-8 Pa pressure region, standard cleaning procedures and mild vacuum baking is sufficient in most instances. Vacuum chambers for use in the lower 10-9-10-10 Pa region are frequently pretreated by vacuum firing in order to reduce the hydrogen outgassing, which is the main residual gas in that pressure range. Vacuum firing is a heat treatment of the vacuum vessels in a vacuum oven to 950 °C for l-3 h, depending on thickness of the material, at a pressure less than 10-3 Pa, which results in an outgassing of the material. Heat treatment in ambient air is both simpler and cheaper to perform than vacuum firing. Therefore it is of interest to investigate the feasibility of an air bake as an alternative, to accomplish lower outgassing rates which is discussed in this paper.